Too big to fail? Accounting for predictions of financial distress in English professional football clubs - Plumley, D.; Serbera, J.-P.; Wilson, R. (Journal of Applied Accounting Research, 2020)
Purpose: This paper analyses English Premier League (EPL) and English Football League (EFL) championship clubs during the period 2002-2019 to anticipate financial distress with specific reference to footballs' Financial Fair Play (FFP) regulations.